Parent-teen communication about sex in urban thai families - Orratai Rhucharoenpornpanich (2018)
This study describes sexual communication among Thai parents and their teens and identifies variables related to communication about sex in urban Thai families. Data were derived from 420 families whose teenage children ages 13-14 years were randomly selected using the probability proportional to size technique. Interviews were conducted with 1 parent and 1 teenage child in each family. In-depth interviews were also conducted in 30 parents and teens drawn from the same 420 families. Results showed that parents were most likely to talk with their teens about body changes and dating; however, less discussion about sex-related issues, birth control, and HIV/AIDS occurred. More daughters than sons reported frequent discussions with their parents about sex. Parents who believed their teens had been involved in sexual activity were more likely to talk about HIV/AIDS and the difficulty of teenagers having babies, instead of talking about sexual intercourse or when to start having sex. Multiple regression analysis indicated that gender of the child (female), parental religiosity, and parental perception of teen sexual activity were significant predictors of increased sexual communication in Thai families. The findings suggest a need for approaches designed to facilitate communication skills about sex-related issues among Thai parents. © 2012 Taylor and Francis Group, LLC.